Diffusion coefficient of tin(II) methanesulfonate In Ionic Liquid and Methane Sulfonic ccid (MSA) solvent - Yang, K.K.; Basirun, Wan Jefrey; Koay, H.L.; Ebadi, M.; Mahmoudian, M.R. (Springer Verlag (Germany), 2011)
Voltammetry and chronoamperometry for the electrodeposition of tin from Tin(II) methane sulfonate mixed with ionic liquid and methane sulfonate acid at room temperature was studied. Cyclic voltammetry shows redox waves of Tin(II), which proves that the electrodeposition of tin from Tin(II) methane sulfonate is a diffusion-controlled process. The diffusion coefficient of Tin(II) ions in the solvent mixture showed good agreement from both voltammetry and chronoamperometry results. The diffusion coefficient of Tin(II) in the mixture was much smaller than in aqueous solution, and it depends on the anion of the ionic liquid. © The Minerals, Metals & Materials Society and ASM International 2011.